(untitled) (Medical Forum Monthly, 2024)
Background: - Exhumation is conducted around the globe when foul play is suspected. In developed world and in some developing countries this procedure is also carried out for identification purposes as well as in insurance claims, and some other civil suits. Objective: To determine the cause of death in exhumed bodies. Study design: Prospective, descriptive. Place & Duration of Study: The Study was conducted in the department of Forensic Medicine, Chandka Medical College, Larkana (CMCL) from Jan:2001 to Dec:2010. Materials and Methods: A total of 125 bodies were exhumed in various districts of upper Sindh by exhumation board, constituted by Director General Health Services Hyderabad. At the site of graveyard, bodies were digged out. After identification of deceased by near relatives, the bodies were thoroughly examined, viscerae taken for histopathological and chemical analysis, and cause of death determined by consensus in almost all cases. Results:- The most common cause of death was firearm injuries 37 (29.6%), followed by blunt trauma 15 (12%), sharp weapon injuries 09 (7.2%), drowning 09 (7.2%), poisoning 07 (5.6%) strangulation 06 (4.8%), infanticide 06 (4.8%). In about 1/3 of cases cause of death could not be decided due to advanced stage of decomposition. Conclusion: Majority of victims were young males & firearm injury was the commonest cause of death.